Bullying as a Menace among Adolescents - Shankar, S.Prabu (JOURNAL OF INDIAN EDUCATION, 2019)
This paper is an attempt to study bullying in its varied forms, the psyche of the bullies, their personality traits, their motives and the other major factors inducing bullying. Nowadays, the term ‘bullying’ has become a fashionable and describable term commonly used by the school and college goers, parents, teachers and educational administrators most often without perceiving the seriousness and intensity of the problem involved with the term. What most often starts as bullying intensifies in course of time resulting in very serious tendencies resulting in danger to the person cornered. Bullying behaviour is commonly found among adolescents at their secondary and higher secondary level in various forms such as intimidation, mistreatment, oppression, harassment, victimisation, maltreatment, hounding, discrimination etc., and sometimes among the college goers in the form of ragging, stalking, prejudice, dominance etc., In this study, a sample of around 518 students in their adolescence studying at the secondary and higher secondary levels were identified based on their bully behaviour. Students who were being bullied were also identified and taken as samples. Around 64 teachers were met during the process of this study and an unstructured questionnaire was administered to them in order to analyse their adequacy of knowledge regarding the bullying behaviour of students, around 40 per cent of the teachers were found to have adequate knowledge of the bullying behaviour of students. From the study it was observed that on an average around 7 per cent to 10 per cent of students who belong to the peer group— non-achieving, physically dominant individuals involve in serious bully behaviours.